PATH-32. CONCORDANCE FOR CDKN2A/B LOSS AND TERT MUTATION IN WHO 2021 CLASSIFICATION GRADE 3 MENINGIOMAS: A RETROSPECTIVE STUDY. (14th November 2022) - Yuen, Carlen; Pan, Peter; Teasley, Damian; Miller, Michael; Sun, Yu; Canoll, Peter; Joanta-Gomez, Adela; Bargo, Alicia; Iwamoto, Fabio
Abstract: BACKGROUND: The new WHO 2021 classification included CDKN2A/B loss and TERT mutation as new criteria for Grade 3 meningiomas, but excluded H3K27me3 loss. Malignant behavior may be influenced by DNA methyltransferases (DNMT3A). SUFU mutations may carry a predisposition for multiple meningiomas. METHODS: In this retrospective study, 228 patients with Grade 2, Grade 3 or recurrent Grade 1 meningiomas with resections from 1990 to July 2021 at Columbia University Medical Center were assessed for recurrence, histologic features, and molecular alterations. RESULTS: Of 228 patients with meningiomas, 9 were recurrent Grade 1, 9 were Grade 1 transformed to Grade 2, 109 were non-recurrent Grade 2, 77 were recurrent Grade 2, 13 were transformed Grade 2 to Grade 3, and 5 were non-recurrent Grade 3 and 6 were recurrent Grade 3. Median follow-up was 42.0 months. Of the recurrent/transformed tumors, 89 were radiation-resistant. Average mitotic counts for non-recurrent Grade 2 vs. recurrent/transformed Grade 2 and non-recurrent Grade 3 vs. recurrent Grade 3 meningiomas were 4 vs. 5, 24 vs. 27 mitoses/10HPF, respectively. Of 36 meningiomas evaluated with NGS, the most common alterations was NF2 (20/36). CDKN2A/B was lost in 5 meningiomas, three with Grade 2 that transformed to Grade 3 and two with recurrent disease. TERT was mutant in 3/36, 2 of which were Grade 2 that transformed to Grade 3 meningiomas. H3K27M me3 was tested by IHC in 4 patients, 3 with retained staining, all of whom did not recur and 1 with loss of staining in a Grade 1 transformed to Grade 2. DNMT3A was found in 2 tumors, both radiation-induced. SUFU occurred in 3/16, one of each grade, all solitary. CONCLUSION: In our limited cohort, we observed concordance with the new WHO 2021 criteria for Grade 3 meningiomas